Coronary Endarterectomy: a Case Control Study and Evaluation of Early Patency Rate of Endarterectomized Arteries - Costa,Mario Augusto Cray da (2020)
Abstract Objective: To compare two groups of patients - the coronary endarterectomy group, with patients undergoing coronary artery bypass grafting (CABG) with coronary endarterectomy (CE), and the control group, with patients undergoing CABG without CE. We analyzed the rate of major outcomes (perioperative acute myocardial infarction [AMI], stroke, and mortality) and minor outcomes (time of cardiopulmonary bypass [CPB], time of aortic clamp, and postoperative length of hospital stay). We also determined the rates of early graft patency in patients undergoing CE. Methods: We reviewed a database of patients submitted to CABG, with or without associated CE, between January 2011 and June 2017. Twenty-five patients submitted to CE were compared with 201 patients submitted only to conventional surgery; the two groups presented similar preoperative characteristics and all the European System for Cardiac Operative Risk Evaluation (EuroSCORE) II variables did not presented statistically significant difference. We considered statistically significant values of P< 0.05. Results: There was no statistically significant difference in relation to time of post-surgical hospitalization (P=0.8139), incidence of perioperative AMI (P=0.2976), stroke (P=0,2976), and mortality rate (P=1.0000), but endarterectomy was associated with longer aortic clamping time (P=0.0004) and CPB time (P=0.0030). The rate of patency evaluated in patients submitted to endarterectomy (78,95%) was compatible with that described in the literature. Conclusion: In this sample, coronary endarterectomy was associated with the rate of early graft patency similar to that of the literature, with morbidity and mortality rates similar to those of conventional surgery.